Labelled loans, credit constraints and sanitation investments - Britta Augsburg; Bet Caeyers; Sara Giunti; Bansi Malde; Susanna Smets (Institute for Fiscal Studies (IFS), 2019)
Credit constraints are considered to be an important barrier hindering adoption of preventive health investments among low-income households in developing countries. However, it is not obvious whether, and the extent to which, the provision of labelled micro-credit (where the loan is linked to the investment only through its label) will boost human capital investments, particularly when it is characterised by other attractive attributes, such as a lower interest rate. We study a cluster randomised controlled trial of a sanitation micro-credit program in rural India, which made available lower interest loans for sanitation. The loans were linked with sanitation through their name only. The loans were not bundled with any toilet, and loan use was weakly monitored, but not enforced. Hence it is not directly obvious that the loan should boost sanitation investments. A simple theoretical framework indicates that the intervention could increase sanitation ownership through three channels - relaxation of credit constraints, salience of the loan label, or the lower interest rate. Our empirical evidence, combined with model predictions, allows us to conclude that the loan label (which to date has not received much attention in the literature) significantly impacts households borrowing and investment behaviour. Labelling loans is thus a viable strategy to improve uptake of lumpy preventive health investments.
Keywords: O16; D14; G41; I12; 330